Design and General Characteristics of ’Ghan Dol’ (Four Seam Trawl) Operated from Ratnagiri, India - V. G. Yewale; M. M. Shirdhnakar; A. S. Mohite; S. K. Barve; R. H. Rathod; K. J. Chaudhari; S. V. Patil; B. M. Yadav; S. M. Wasave; B.V. Naik (Journal of Indian Fisheries Association, 2021)
Four seam trawl locally known ’Ghan dol’, operated from Ratnagiri, Maharashtra was observed with five belly sections of overall length ranges from 25m to 30m. Wings of the net were triangular in shape with a mesh size variation between 35and 40 mm. Outer length Upper wing panel was 6.50 m while outer length of lower wing panel was 5.97 m. Mesh sizes recorded for overhang section were 40 mm which is same as that of wing section. Mesh sizes for belly sections of the net ranged from 25-40 mm. Cod end mesh size of trawl operated from Jaigad, Kasarveli, Mirkarwada and Purnagad landing centres was recorded as 20 mm. In Ratnagiri, four seam trawl are used mainly to catch shrimps.